2011
DOI: 10.1002/polb.22336
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of fatigue failure mechanisms in polymer fuel cell membranes

Abstract: The swelling‐driven fatigue behavior of polymer fuel cell membranes during relative humidity (RH) cycling is investigated. In particular, swelling‐induced membrane stresses are obtained from a numerical model simulating fuel cell RH cycle tests, and compared to the lifetimes obtained experimentally from tests conducted in the absence of electrochemical effects. A strong correlation between the lifetimes of the membranes in the actual tests and model results is obtained. In general, higher RH (or swelling) ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 62 publications
3
69
0
Order By: Relevance
“…Even though in fuel cells the assembly pressures are on the order of a few MPa, the membrane, or part of it, could experience higher stresses due to the additional geometric constraints arising from the cell design. 4,5,[19][20][21][22] Moreover, hydration of the membrane generates additional compressive stresses of up to 10 MPa in the constrained regions of the membrane. 4,5,20,21 (More information on compression testing of membranes can be found in our previous studies).…”
Section: F34mentioning
confidence: 99%
See 2 more Smart Citations
“…Even though in fuel cells the assembly pressures are on the order of a few MPa, the membrane, or part of it, could experience higher stresses due to the additional geometric constraints arising from the cell design. 4,5,[19][20][21][22] Moreover, hydration of the membrane generates additional compressive stresses of up to 10 MPa in the constrained regions of the membrane. 4,5,20,21 (More information on compression testing of membranes can be found in our previous studies).…”
Section: F34mentioning
confidence: 99%
“…4,5,[19][20][21][22] Moreover, hydration of the membrane generates additional compressive stresses of up to 10 MPa in the constrained regions of the membrane. 4,5,20,21 (More information on compression testing of membranes can be found in our previous studies). [23][24][25] Small-angle X-Ray scattering (SAXS).-SAXS experiments of the membranes were performed in beamline 7.3.3 at the Advanced Light Source (ALS) at Lawrence Berkeley National Laboratory (LBNL).…”
Section: F34mentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged membrane exposure to these stresses causes mechanical rupture via fatigue (cyclic stress) and/or creep (constant stress) phenomena. 12,13,20,23,33 Moreover, mechanical properties of the membrane deteriorate during chemical degradation;…”
mentioning
confidence: 99%
“…either facing the flow channel or in direct contact with the channel land). Calculations made by Kusoglu et al [237] revealed that residual stresses can be up to 10MPa which may lead to delamination of the membrane and the gas diffusion layer and similarly the high in-plane stresses were associated to crazing and its growth. The simulations of [296] suggest that in-plane stresses are much higher under the land regions than under the flow channels at any level of relative humidity of the reactant gases.…”
Section: Membrane Swellingmentioning
confidence: 99%